Composition of selected heavy metals in road dust from Kuala Lumpur city centre - Hafizan, Juahir; Nur Mun’im, Mohd Han; Mohd Talib, Latif (2014)
This study was carried out in order to determine the concentration of heavy metals, e.g., lead (Pb), cadmium (Cd), copper (Cu), zinc (Zn), iron (Fe), manganese (Mn), nickel (Ni) and chromium (Cr) in road dust in Kuala Lumpur’s city centre. Samples were collected from four sampling locations, each of which had four sampling points and three replications. Heavy metals from different fractions of particles separated by different diameter sizes: d\63 lm (Fraction A), 63\d\125 lm (Fraction B) and 125 \d\250 lm (Fraction C) were analyzed using inductively coupled plasma mass spectrometry. The results from this study showed that concentration of heavy metals was dominated by the smallest particle size: \63 lm and that Fe was the most abundant heavy metal overall, followed by Cu[Mn[Zn[Pb[Ni [Cr [Cd. The fact that Cd had the highest enrichment factor value (EF) for all particle sizes indicates that anthropogenic activities contributed to the presence of this metal. There was also a higher EF value for heavy metals in small particle (Fraction A), compared to Fraction B and C, which suggests that fine particles were being produced through anthropogenic activities. Cluster analysis and principal component analysis demonstrated the likelihood of the heavy metals detected in the road dust, originating from road traffic and industrial activities.